Relationship between laryngomalacia and sleep-related breathing disorders in infants with brief resolved unexplained events - Luana Nosetti; Francesca De Bernardi; Eleonora Sica; Patrizia Latorre; Massimo Agosti; Paolo Castelnuovo; Giulia Cocciolo; Marco Zaffanello (Hygeia Press di Corridori Marinella, 2021)
Introduction: Brief resolved unexplained events (BRUE) occur during infancy. It is characterized by one or more symptoms, including skin color change, shortness of breath and unresponsiveness. Laryngomalacia is the most frequent cause of stridor in infants and results in the collapse of the supraglottic structures during inspiration and intermittent obstruction of the upper airways. To our knowledge, the relationship between BRUE and laryngomalacia has been little investigated. Methods: The medical records of 448 children (age < 12 months) treated for BRUE between July 2011 and March 2018 and followed up until March 2020 were retrospectively reviewed. Endoscopic evaluation was performed using a flexible fibrolaryngoscope. All patients underwent a brief polysomnography and 24-h cardiorespiratory monitoring. Cardiorespiratory and oxygen saturation monitoring was continued at home; 94% of patients underwent follow-up. Results: Laryngeal fiberoptic endoscopy revealed laryngomalacia in 11% of children with a clinical history of BRUE. Laryngomalacia was associated with obstructive/mixed apnea in 67%. Home cardiorespiratory monitoring showed a gradual reduction in the number of respiratory events during follow-up and complete resolution of laryngomalacia in 88% of patients. Conclusions: This is the first report that showed follow-up data from cases of BRUE with laryngomalacia. The improvement in laryngomalacia alone, although not complete, was sufficient to improve obstructive events.